Hypertension in the Russian population during the COVID-19 pandemic: sex differences in prevalence, treatment and its effectiveness. Data from the ESSE-RF3 study - Yu. A. Balanova; O. M. Drapkina; V. A. Kutsenko; A. E. Imaeva; A. V. Kontsevaya; S. A. Maksimov; G. A. Muromtseva; M. B. Kotova; N. S. Karamnova; S. E. Evstifeeva; A. V. Kapustina; O. A. Litinskaya; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the epidemiological characteristics and changes of hypertension (HTN), as well as factors associated with HTN in the Russian population aged 35-74 years.Material and methods. The Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study examined a representative sample of the population aged 35-74 years of 15 Russian regions with a response >70% (n=28611). Modular design questionnaire was used. Blood pressure (BP) was measured twice after a 5-minute rest in a sitting position on the right arm with an Omron blood pressure monitor. There were following criteria for hypertension: systolic blood pressure (SBP) ≥140 mm Hg and/or diastolic blood pressure (DBP) ≥90 mm Hg, and/or antihypertensive therapy. The effectiveness of treatment was considered the proportion (%) of people who achieved target blood pressure values among those being treated, while the control was considered the proportion (%) of patients with a BP <140/90 mm Hg of the total number of hypertensive patients. HTN changes were studied in a single age range of 35-64 years with the inclusion of materials from the ESSE-RF (2012-14) and ESSE-RF2 (2017) studies, carried out using the same methodology as ESSE-RF3. Statistical analysis was carried out using the open-source R 3.6.1 environment. Analysis of the association between factors and a binary variable was performed using logistic regression. The significance level for all tested hypotheses was 0,05.Results. According to ESSE-RF3, the average levels of SBP and DBP in the population were 131,9±18,7 and 84,4±10,9 mm Hg, respectively, while the proportion of those with BP ≥140/90 mm Hg — 38,8% (men: 44,8%, women: 33,9%). Prevalence of hypertension was 53,9% (men: 56,0%, women: 52,1%), awareness — 77,7% (men: 71,5%, women: 82,3%), while the treatment received 63,4%, significantly higher among women than among men: 72,3 vs 53,3%. The effectiveness of treatment was 44,0%, higher among women compared to men (48,2 vs 37,4%). In addition, 27,9% of patients have controlled HTN.Conclusion. The problem of controlled HTN in Russia remains unresolved in the 21st century. The following significant sex differences remain: the prevalence of HTN is higher among men, but awareness of the disease, treatment rate and its effectiveness are lower compared to women.